3-phase Technicium-99m bone scanning in patients with pain in the hip region after cemented total hip replacement: a multicentre series of 100 cases. Issue 3 (May 2018) - Hill, Daniel S; Naim, Soulat; Powell, Roy J; Kinsella, Denis; Toms, Andrew D; Howell, Jonathan
Introduction: The aim of this study was to assess the benefit of a Technetium-99M (HDP) 3-phase bone scan (TPBS) as an additional diagnostic test in the evaluation of pain in the hip region following cemented total hip replacement (THR) surgery. Methods: A retrospective study over a 24-month period was performed comprising 100 patients investigated with a TPBS. Investigations were summarised and analysed, and were classified as entirely normal, possibly abnormal, and definitely abnormal. Results: 45% (45) of TPBSs were reported as being entirely normal, 50% (50) as possibly abnormal, and 5% (5) as definitely abnormal. During the 24-month study period 230 revision THR procedures were performed at our institution; 10% (24) were investigated with TPBS and 90% (206) were not. 29% (7/24) of patients investigated with a TPBS that subsequently underwent revision THR surgery had an entirely normal preoperative TPBS. 84% (38) with an abnormal TPBS were managed conservatively. A TPBS had a sensitivity of 29% (95% confidence interval (CI), 13%-51%) and a specificity of 50% (95% CI, 38%-62%) in the detection of infection, or loosening with concurrent infection. Conclusion: A TPBS should only be considered following clinical evaluation, serological investigation, diagnostic imaging and microbiological analysis of fluid obtained from arthrocentesis by a specialist revision arthroplasty surgeon. A TPBS may be useful in the situation where abnormal serology is present, but where repeated joint aspirations samples are inconclusive.